What leads users to recommend, not just use? Unpacking service quality, labor perceptions, and conscious consumer choice in food delivery apps - Serrano-Malebrán, Jorge; Molina, Carlos (Frontiers in Sociology, 2025)
This study examines how perceptions of service quality, working conditions, and socially conscious consumption influence the intention to use and recommend food delivery applications in Chile. Drawing on the Stimulus–Organism–Behavior–Consequence (SOBC) theoretical framework, this study simultaneously analyzed functional factors, namely efficiency, fulfillment, system availability, and privacy, and ethical-social factors, such as perceived working conditions. A quantitative design was employed with a sample of 416 users, evaluating the constructs through validated scales and applying Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that service quality is the strongest predictor of intention to use and positively affects both the intention to recommend and socially conscious consumption. In contrast, working conditions do not directly influence intention to use but positively impact intention to recommend and socially conscious consumption. Socially Conscious consumption, in turn, influences only the intention to recommend and not the intention to use. The findings confirm that, in digital contexts, socially conscious consumers tend to express their values more through recommendations than through purchase decisions. These insights offer relevant implications for academia and practice, suggesting that integrating operational efficiency with fair labor practices can strengthen the sustainability of platform-based business models.